Studi Kualitatif Pemberian Air Susu Ibu (ASI) pada Bayi Usia 0-6 Bulan di Wilayah Puskesmas Patebon II Kabupaten Kendal - Shinta Ayu Nani; J Jumiatun (Indonesian Journal on Medical Science, 2023)
One strategy for identifying, preventing and overcoming nutritional problems is to provide exclusive breastfeeding to infants from birth to six months of age. Exclusive breastfeeding coverage in Kendal Regency in 2021 of 55% has exceeded the 2021 Strategic Plan target of 45%, but the achievements at the Patebon II Health Center are ranked second lowest for two consecutive years at 25% (2021) and 19.09% (2020). ) of 30 Community Health Centers in Kendal District. This study aims to describe the provision of Mother's Milk (ASI) to infants aged 0-6 months at the Patebon II Health Center, Kendal Regency. This type of qualitative research uses in-depth interviews to collect comprehensive data on breastfeeding in infants aged 0 to 6 months. The sample in this study were 10 main informants, mothers who had children aged over six months and two triangulation informants, namely the coordinating midwife and nutritionist. The results of the study showed that all mothers understood about exclusive breastfeeding, not all of them were prepared for the breastfeeding process, the anemia condition of the mother could still give exclusive breastfeeding, IMD had an effect on the subsequent breastfeeding process, sore nipples and swollen breasts were two common problems related to breastfeeding for mothers, 70% of mothers give exclusive breastfeeding, all mothers have received support from husbands, health workers and families to give exclusive breastfeeding to their babies. good.